Verjuntas : cineclube de mulheres nas ocupações urbanas em Uberlândia/MG - Iara Helena Magalhães (2024)
In recent past, in the city of Uberlândia-MG, a historic stronghold of agribusiness and UDR (União Democrática Ruralista), around 10 thousand families faced public authorities, real estate sectors, politicians and the media, in movements to fight for a home. In this composition plan, women living in three occupations were invited to found the Women’s Film Club Seetogether. The emergence of a film club on the outskirts of the city during the pandemic period is, in itself, an unprecedented event, especially because it was organized by a team of homeless women, willing to start a film club activity, which triggers aesthetic preferences, political options and specific situations of strugle and daily work routine in communities. Cinema experience in occupations, with homeless women for the first time, whatching short films directed by women, confirms the following proposition: women in occupations produce life in difficult and unfair conditions, however, with attention, with joy and, why not to say, with vigor they set out to see the films as a challenge: they challenge the order of cities, which has no place for them. The epistemological possibility that every cultural practice is applied primarily to the body is defended in this research, in which the sensitive is apprehended, written, transcribed and assembled through interrelations between films and their appropriation, between theoretical-methodological application and the production of an affective cartography, between the sensitive cards and the drawings and photos produced by women, between the times of formative moments of experience and those of the memory of writing the reports. By bringing together a multiplicity of thoughts, authors and films, we provoke movements, among them, listening to some invisibilities – homeless women and communities on the edge of the asphalt city –, breaking the separation between those who know and those who is supposedly ignorant. This thesis can be understood as a field of struggle for homeless women, reverberating in the production of new territories of existence for them and for communicational research, through the production of new sensitive epistemological arrangements, in everyday life, in political action, in their existente.